April Fool! watch out at school! - De Groat, Diane (New York : HarperCollinsPublishers, 2009)
Gilbert is tired of falling for everyone else's pranks and decides he is going to pull off the best April Fool's Day joke ever.
"Gilbert and friends"--Dust jacket.
Booklist.
2.3
K-3
Keywords: April Fools' Day -- Juvenile fiction; Practical jokes -- Juvenile fiction; Schools -- Fiction; April Fools' Day -- Fiction; Picture puzzles; Practical jokes -- Fiction; Schools -- Fiction; April Fools' Day -- Fiction; Picture puzzles; Practical jokes -- Fiction; School stories